Surface and Interface Characterization of Lithium Metal Anodes for the Application in Solid-State Batteries - Otto, Svenja-Katharina; Justus Liebig University Giessen (My University, 2022)
The use of lithium metal anodes (LMAs) in solid state batteries (SSBs) is a promising approach to develop secondary batteries with high energy and power densities. These are needed to meet the demand of rapidly developing markets like the one for electric vehicles. Since LMAs provide an about ten times higher theoretical capacity than common graphite intercalation anodes, they are regarded as ideal future anode material. However, in combination with liquid electrolytes, severe safety issues arise for secondary batteries with LMAs due to dendrite formation and resulting short circuits. In contrast, solid electrolytes (SEs) are expected to be a safe solution, as they are more stable at high temperatures and in the case of inorganic SE not flammable. Still, also for SEs, the implementation of LMAs is challenging. Especially the lithium|SE (Li|SE) interface properties are regarded as a key challenge for the successful use of LMAs in secondary batteries. One well-described problem in this context is the reactivity of lithium towards most SEs, which can lead to interphase formation and consequently to high interfacial resistance, as well as lithium loss. Another central factor is mostly unknown or neglected: Due to the high reactivity of lithium, lithium foil and other exposed lithium surfaces are always covered with some kind of reaction layer, which can have a detrimental effect on the interfacial properties in the battery. For LIBs with liquid electrolyte the effect of this surface passivation layer has already been evaluated and proven to be highly important. In case of SSBs, the effects are probably even more severe, as the lithium surface film cannot dissolve into the electrolyte. Consequently, a detailed investigation is needed. Therefore, this doctoral thesis focuses on the characterization of lithium surfaces, their changes under handling and storage conditions which are typical for battery research, and how these changes affect the anode interface resistance in SSBs. First, a reliable characterization strategy with X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry (ToF-SIMS) was developed. The characterization described in literature so far has often been insufficient in terms of experimental design and data interpretation due to several pitfalls. In the present work, these pitfalls were identified, explained and detailed guidelines for reliable lithium surface characterization are given. Based on this, lithium foil was characterized after glovebox storage under various conditions. The steady growth of the lithium surface passivation layer could be attributed to water contaminations in the glovebox atmosphere. Next, the impact of the layer thickness was investigated with a model SSB, finding that the anode interface resistance increases significantly with the presence of an only nanometer-thick passivation layer. The SE roughness and the cell preparation pressure were found to have a strong effect on the resulting interface resistance. In addition, the Li|SE interphase formation was investigated with ToF-SIMS. It is shown that ToF-SIMS can reliably indicate the stability of Li|SE interfaces and can provide information on the microstructure of the interphases. The combination with atomic force microscopy allowed to determine the thickness of forming interlayers, which were thicker than previously reported. Overall, the results of this doctoral thesis expand the knowledge about lithium surfaces, as well as interfaces in SSBs and are one step towards the implementation of LMAs in secondary batteries. The results are a good base for reliable LMA characterization in general and give an improved understanding of the reactivity of lithium surfaces towards atmospheric gases as residues in gloveboxes. Notably, the importance of lithium surface passivation layers was demonstrated for SSBs, what was not considered in literature before. Furthermore, ToF-SIMS was established as a complementary technique for Li|SE interface characterization, expanding the possibilities to obtain a complete picture of the interfaces in SSBs and helping to design tailored modifications.
Keywords: ddc:540